1999
DOI: 10.1136/oem.56.4.284
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects on the olfactory system of exposure to hydrogen sulphide.

Abstract: Objective-To study chronic eVects of hydrogen sulphide (H 2 S) on cranial nerve I (nervi olfactorii), which have been only minimally described. Methods-Chemosensations (smell and taste) were evaluated in eight men who complained of continuing dysfunction 2-3 years after the start of occupational exposure to H 2 S. Various bilateral (both nostrils) and unilateral (one nostril at a time) odour threshold tests with standard odorants as well as the Chicago smell test, a three odour detection and identification tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 4 publications
0
30
0
Order By: Relevance
“…Data on the clinical course of occupational-related olfactory impairment are largely insufficient, even if some results suggest the possibility of both, a reversible effect, as in workers exposed to acrylates (Schwartz et al 1989) or to solvent mixtures (Sandmark et al 1989), or a permanent deficit, as observed in exposure to hydrogen sulfide (Hirsch and Zavala 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Data on the clinical course of occupational-related olfactory impairment are largely insufficient, even if some results suggest the possibility of both, a reversible effect, as in workers exposed to acrylates (Schwartz et al 1989) or to solvent mixtures (Sandmark et al 1989), or a permanent deficit, as observed in exposure to hydrogen sulfide (Hirsch and Zavala 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Hopefully, such testing will continue to provide information of use in monitoring hazardous environments and mitigating their adverse influences on this important sensory system. Cadmium dust/fumes 73 exposed; 43 non-exposed >maximum allowed for chronic occupational exposure Anosmia in 45.2% of exposed, 4.6% of non-exposed Blast injection Hirsch and Zavala (1999) …”
Section: Discussionmentioning
confidence: 99%
“…The same mechanism may cause pharyngeal soreness, gingivitis, rhinitis, and eyes irritation. On chronic exposure, this also might cause gingival and periodontal disease among people who work in environment with presence of H 2 S. Acute, subchronic, and prolong exposure to H 2 S might also cause neuronal olfactory damage, loss of smell sensation, and rhinitis which was reported in previous studies on human, rats, and mice [4,7,14,15]. At lower concentrations, H 2 S was found to cause eye mucosal irritation, and keratoconjunctivitis called 'gas eye', and at higher concentrations there was risk of pulmonary edema [16].…”
Section: Discussionmentioning
confidence: 99%
“…This causes reversible inhibition of aerobic metabolism leading to cellular anoxia [3]. Olfactory deficits (hyposmia) with both a delayed and immediate onset have also been documented following repeated exposures to sublethal doses of H 2 S in workers at a refinery construction site [4]. H 2 S odor was strongly associated with reports of alteration of daily activities, negative mood states, mucosal irritation, and upper respiratory symptoms [5].…”
Section: Introductionmentioning
confidence: 99%